Clinical evidence of therapy for genital psoriasis by biologic agents - Evgeny V. Sokolovskiy (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Data in the scientific literature on the use of biologic therapy in localized forms of psoriasis elucidate mostly the problems of treatment of palmoplantar, scalp psoriasis and nail psoriasis. At the same time, the number of scientific data on the effect of biological therapy on genital psoriasis is extremely limited. Important that the quality of life on patients with genital psoriasis has very low level, which indicates a significant influence on the psychological and social well-being. At the same time, the limited number of therapeutic approaches makes this problem even more urgent. Unfortunately, special clinical trials for such patients are rather an exception. Ixekizumab has been reported an effectiveness for patients with anogenital psoriasis. New data on the comparative efficacy of ixekizumab and secukinumab give hope us for new opportunity for the treatment of genital psoriasis.